2007
DOI: 10.1002/pon.1263
|View full text |Cite
|
Sign up to set email alerts
|

Posttraumatic stress disorder among parents of children on cancer treatment: a longitudinal study

Abstract: The main aim of this study was to investigate the occurrence of cancer-related posttraumatic stress disorder (PTSD) among parents of children on cancer treatment. A longitudinal design with assessments at one week (T1), two (T2), and four (T3) months after the child's diagnosis was used. Two hundred and fourteen parents (107 mothers, 107 fathers) participated at T1-T3. The PTSD Checklist Civilian (PCL-C), a self-report screening instrument for PTSD, was answered by parents over the telephone. According to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
102
3
5

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 125 publications
(126 citation statements)
references
References 34 publications
16
102
3
5
Order By: Relevance
“…Participants were invited to take part in a RCT investigating the efficacy of an Internetbased guided self-help intervention. In the current sample, the mean level of PTSS was 43.5 (SD = 13.6), which is higher than was found in a previous Swedish cohort study of parents of children diagnosed with cancer, which also used the PCL-C, and for which the mean level of PTSS was 36.5 (SD = 12.1) 2 months after diagnosis (Pöder et al, 2008). Furthermore, one could argue that the enrollment rate was poor, but it might also be that the enrollment rate adequately reflected the proportion of parents of children of children on cancer treatment who experience a need for psychological support.…”
Section: Discussioncontrasting
confidence: 47%
See 2 more Smart Citations
“…Participants were invited to take part in a RCT investigating the efficacy of an Internetbased guided self-help intervention. In the current sample, the mean level of PTSS was 43.5 (SD = 13.6), which is higher than was found in a previous Swedish cohort study of parents of children diagnosed with cancer, which also used the PCL-C, and for which the mean level of PTSS was 36.5 (SD = 12.1) 2 months after diagnosis (Pöder et al, 2008). Furthermore, one could argue that the enrollment rate was poor, but it might also be that the enrollment rate adequately reflected the proportion of parents of children of children on cancer treatment who experience a need for psychological support.…”
Section: Discussioncontrasting
confidence: 47%
“…Furthermore, one could argue that the enrollment rate was poor, but it might also be that the enrollment rate adequately reflected the proportion of parents of children of children on cancer treatment who experience a need for psychological support. It has been shown that 28 % of parents of children diagnosed with cancer report symptoms indicating potential PTSD 2 months after their child's diagnosis (Pöder et al, 2008) and that 46 % report a need to meet with a psychologist at the same assessment (Pöder & von Essen, 2009). In the current study, 26 % of the approached parents expressed an interest in participating in the RCT and consented to be contacted.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For others, diagnosis can be an unexpected devastation, a theme repeatedly mentioned by Nicholas et al (3) . Several authors have investigated the post-traumatic stress in parents of children with chronic disease (28,30,34,36,37). Manifestations of stress, such as dissociation, re-experience, hyper-arousal and avoidance, have been identified as most prevalent closer to diagnosis (37) .…”
Section: Diagnosis and Short Termmentioning
confidence: 99%
“…Several authors have investigated the post-traumatic stress in parents of children with chronic disease (28,30,34,36,37). Manifestations of stress, such as dissociation, re-experience, hyper-arousal and avoidance, have been identified as most prevalent closer to diagnosis (37) . Indeed, one-half of that study ' s parents exhibiting acute stress disorder at 1 week had post-traumatic stress disorder diagnoses made at 4 months.…”
Section: Diagnosis and Short Termmentioning
confidence: 99%